Occupational Safety and Health Evaluation Using the Hazard Identification Risk Assessment and Risk Control (HIRARC) Method Based on Ergonomics - Napitupulu, Daniel Willyam; Irwan, Hery (ASTONJADRO, 2026)
PT. XYZ is a medium-sized shipbuilding company engaged in ship repair, maintenance, and new shipbuilding services. The company faces a high potential for workplace accidents in Workshop Area 01, Shelter 05, and the Jetty Area. This study aims to analyze and evaluate workplace hazard potential using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method, based on ergonomic principles. The research methodology employed a quantitative and qualitative approach through observation, interviews, and the distribution of questionnaires to 78 workers. The novelty of this study lies in the integration of ergonomic principles into the HIRARC analysis to assess and control workplace accident risks. The analysis results identified 15 categories of potential hazards, with details as follows: 5 low-risk, 8 moderate-risk, and 2 high-risk hazards. High-risk hazards were identified in grinding and plate-cutting activities, which require immediate control measures. Control measures were implemented through the use of personal protective equipment (PPE), technical engineering, administrative measures, and worker education. This study concludes that the integration of ergonomics into HIRARC effectively helps companies identify and reduce workplace accident risks while improving workplace safety and comfort.